Behavioural Patterns and Their Relationship to Autism Children's Eating Problems - Wailey, Jameelah Raheem Abed; Al- Mollah, Saly Talib Alwan (Journal of Ecohumanism, 2024)
Eating problems in autism children.Behavioural patterns in autism children.The relationship between behavioral patterns and the eating problems of autism children.The indication of differences in behavioural patterns in autism children according to the sex variable (male, female).Indication of differences in the eating problems of autism children according to the sex variable (male, female). The research sample consisted of 150 children and their children from special education institutes in Baghdad. The two researchers prepared behavioral patterns research tools. The scale consists of (26) Paragraph before each alternative paragraph (applicable, not applicable) And the average hypothesis (39) and the measure of eating problems consists of (19) a paragraph before each paragraph three alternatives (always, sometimes rarely) and a hypothetical average (38). The two researchers extracted the authenticity and consistency of the two tools using the statistical pouch and the appropriate means of research objectives. The results showed that they had high levels of eating problems and behavioral patterns. The results showed that there was a statistically significant exclusive correlation between eating problems and behavioral patterns. The calculated correlation value (0.61) was higher compared to Pearson's extreme tabular freeness factor (0.15) at 0.05. (148) .And there is a difference in eating problems depending on the sex variable (Male, female) For the benefit of the female, the two researchers came up with a number of recommendations and proposals..